Targeting highly expressed extracellular HSP90 in breast cancer stem cells inhibits tumor growth in vitro and in vivo. Issue 8 (2nd August 2016) - Stivarou, Theodora; Stellas, Dimitris; Vartzi, Georgia; Thomaidou, Dimitra; Patsavoudi, Evangelia
ABSTRACT: Breast cancer stem cells (BCSC) have been identified in breast carcinoma as CD44 + /CD24 −/low cells, which display tumorigenic activity and have the ability to self-renew, differentiate and metastasize. Previous studies showed that extracellular HSP90 (eHSP90) participates in the invasion and metastatic processes of various cancers including breast cancer. Here, we show for the first time that eHSP90 is over-expressed in mammosphere cultures that are derived from the MDA-MB-231, MDA-MB-453 and MCF-7 breast cancer cell lines. These mammospheres are highly enriched in cells of the CD44 + /CD24 −/low BCSC phenotype and additionally show high expression of the BCSC markers CD49f and Sox2. Thus our results indicate that eHSP90 represents a potential novel BCSC marker. Moreover, we present evidence that eHSP90 is functionally involved in BCSC activity in vitro and in vivo . Selective neutralization of eHSP90, using the monoclonal antibody mAb 4C5, has the capacity to inhibit stem cell activity in vitro because the formation of mammosphere-derived colonies is dramatically reduced in its presence. In vivo, the treatment of mice with mAb4C5 using a prophylactic protocol, significantly inhibited the primary growth of MDA-MB-231 and mammosphere-derived tumors. More importantly, administration of this antibody in a therapeutic protocol caused a statistically significant regression of established tumors derived from MDA-MB-231 originating mammospheres. Tumor regression was even greater when mAb 4C5 was administered in combination with paclitaxel. Overall, our findings implicate eHSP90 as a potential novel BCSC biomarker. Moreover they show that eHSP90 participates in BCSC-derived primary tumor growth. Finally, we provide additional support for the possible therapeutic value of mAb4C5 in the treatment of breast cancer.